Novel duplex TaqMan-based quantitative PCR for rapid and accurate diagnosis of Leishmania (Mundinia) martiniquensis and Leishmania (Mundinia) orientalis, responsible for autochthonous leishmaniasis in Thailand - Kanok Preativatanyou; Nopporn Songumpai; Pathamet Khositharattanakool; Rinnara Ampol; Chulaluk Promrangsee; Chatchapon Sricharoensuk; Kobpat Phadungsaksawasdi; Thanapat Pataradool; Tomas Becvar; Barbora Vojtkova; Petr Volf; Padet Siriyasatien (Current Research in Parasitology and Vector-Borne Diseases)
The World Health Organization has recently declared Thailand a leishmaniasis hotspot in Southeast Asia due to the continuous increase in new symptomatic and asymptomatic cases over the years. This emerging parasitic disease is known to be caused by two autochthonous species of Leishmania belonging to the newly described subgenus Mundinia, namely L. martiniquensis and L. orientalis. In Thailand, clinical cases due to L. martiniquensis typically present with visceral leishmaniasis, whereas L. orientalis mainly causes localized cutaneous leishmaniasis. Although Leishmania species confirmation is essential for clinical diagnosis and treatment planning, the availability of highly accurate and rapid diagnostic methods remains limited. In this study, we developed a duplex TaqMan quantitative PCR assay using newly designed species-specific primers and probes based on sequences from the nucleotide and genome databases of Leishmania spp. retrieved from GenBank. The duplex qPCR assay was optimized to specifically amplify the internal transcribed spacer 1 (ITS1) of L. martiniquensis and the heat shock protein 70 (type I) intergenic region (HSP70-I IR) of L. orientalis with high amplification efficiencies. The performance of the optimized duplex qPCR was evaluated by analyzing 46 DNA samples obtained from cultures, and clinical and insect specimens, consistent with the results of the previously validated 18S rRNA-qPCR and ITS1-PCR. The duplex qPCR could detect both species of Leishmania at a limit of detection of one copy per reaction and did not cross-amplify with other pathogen DNA samples. Standard curves of the singleplex and duplex assays showed good linearity with excellent amplification efficiency. Using conventional ITS1-PCR and plasmid sequencing as a reference standard assay, the duplex qPCR showed diagnostic sensitivity and specificity of 100% and positive and negative predictive values of 100% for both Leishmania species with a perfect level of agreement (kappa = 1.0). The novel duplex TaqMan-based qPCR has shown to be a rapid, cost-effective, and highly accurate diagnostic tool for the simultaneous detection and identification of two autochthonous Leishmania spp. in a variety of clinical and entomological samples. This will greatly facilitate early diagnosis, treatment monitoring, and surveillance, especially in leishmaniasis-endemic areas where sequencing-based diagnosis is not routinely available.